Predictive Value of Zero Calcium Score and Low-End Percentiles for the Presence of Significant Coronary Artery Stenosis in Stable Patients with Suspected Coronary Artery Disease - Vogler, N.; Meyer, M.; Fink, C.; Schoepf, U. J.; Schönberg, S. O.; Henzler, T. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2013)
Purpose: To prospectively investigate the predictive value of a zero calcium score (CS) value as well as age- and sex-adjusted low-end CS percentiles for the presence of significant coronary artery stenosis in stable patients with suspected coronary artery disease (CAD). Materials and Methods: In total, 87 consecutive stable patients with suspected CAD were prospectively enrolled in this study (33 women; 66 ± 10 years). All patients underwent non-enhanced CT for calcium scoring (CSCT) and contrast-enhanced coronary CT angiography (cCTA). Invasive coronary angiography (ICA) served as the reference standard in all patients. Diagnostic performance for the presence of significant stenosis (≥ 50 % diameter) was calculated separately for CS in comparison to cCTA and ICA. Results: ICA identified significant stenosis in 56/87 patients (64 %). The mean CS was 571 ± 599. On a per patient based analysis, the sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) for patients with a zero CS were 98.5 %, 18.2 %, 78.0 % and 80.0 %, respectively, compared to cCTA and 100 %, 16.1 %, 68.3 % and 100 %, respectively, compared to ICA. Low-end age- and sex-adjusted percentiles derived from asymptomatic Caucasian populations showed results comparable to a CS of zero. Conclusion: The prevalence of significant coronary artery stenosis is low in stable patients with suspected CAD and a CS of zero but also in patients below certain low-end age- and sex-adjusted percentile ranks. Thus, CS should be used as a gatekeeper prior to further diagnostic procedures in these patients. A CS value below certain age- and sex-adjusted percentile ranks seems to be of identical diagnostic value to a CS of zero in stable patients.
Keywords: coronary calcium score; coronary artery disease; invasive coronary angiography; coronary CT angiography